MENAKAR PARADIGMA KEAMANAN NASIONAL MELALUI ANALISIS ISI TERHADAP UNDANG-UNDANG No. 17 TAHUN 2011 TENTANG INTELIJEN NEGARA - Dian Nursita, Surwandono, Ratih Herningtyas , (Fakultas Ilmu Sosial Ilmu Politik Pr, 2018)
The evolution of both domestic and international security issues have influenced the development of Indonesia intelligence and its agencies. Indonesia intelligence reform is marked by the establishment of Badan Intelijen Nasional or Indonesia National Intelligence Agency and the enactment of Law Number 17 of 2011 on The State Intelligence. In order to reveal the paradigm used in determining the direction of Indonesiaâs national security policy, this paper analyzes Law Number 17 of 2011 on The State Intelligence using content analysis method. Analysis among indicators representing three paradigms; realism, liberalism, and constructivism shows that Law Number 17 of 2011 on The State Intelligence is strongly influenced by realist paradigm.